Становлення і розвиток кооперативних організацій споживачів у країнах Європи (друга половина ХІХ – початок ХХІ ст.) - Легошина, Олена Леонідівна (Східноєвропейський національний університет імені Лесі Українки, Луцьк, 2017)
Основним напрямом дослідження є здійснення комплексного історико-економічного аналізу процесу становлення і розвитку кооперативних організацій споживачів у країнах Європи в період другої половини ХІХ – початку ХХІ століття та розробка науково-практичних рекомендацій щодо підвищення ефективності функціонування кооперативного сектору на вітчизняному ринку споживчих товарів і послуг. Розглянуто та визначено економічну сутність і функціональні особливості кооперативів споживачів. Проведено історико-економічний аналіз, систематизацію праць західних економістів другої половини ХІХ – початку ХХ століття та ідентифіковано історичні періоди становлення і розвитку кооперативів споживачів.Охарактеризовано сучасні тенденції розвитку кооперативних організацій споживачів у країнах Європи. In this thesis the essence of economical nature of cooperative organizations of consumers is disclosed. It is found out that the term “cooperative organization of consumers” doesn’t have a single meaning. The proposal to look at it both in the narrow and broadest sense of the word was driven by this fact. In the narrow sense of the word the notion “cooperative organization of consumers” is worth being looked at as a cooperative organization which serves to provide members-owners with consumer goods, by means of bulk purchases or by means of own production. In the widest sense of the word the term should be looked at as cooperative organization which provides members – consumers with any necessary service (in some cases several services, depending on its’ tasks). Based on the existing definitions there was generalized scientific definition of the term “cooperative organizations of consumers” created, when you look at them as at non-profit economic organizations, which meet international cooperative principles and have the satisfaction of most diverse consumer needs of members-owners as a target. The analysis of proceedings of the representatives of Ukrainian and foreign cooperative view as well as analysis of publications in cooperative periodicals of the second half of 19th – beginning of 21st century, regarding the problems of genesis and development of cooperative organizations of consumers is done. As a result of analysis of financial mechanism of functioning of the Rochdel model of the consumer goods society, the sources of its’ income generation were identified: reimbursement of costs for the purchase of goods by its’ members and the organization of cooperative trade, overpayment by members while buying goods at an average market price (was subject to partial return after the end of the financial year) as well as receipts from non-members of the cooperative when they purchase goods. The conclusion about the importance of the introduction in Ukrainian practice of non-financial cooperative organizations of consumers, which are effective in the European Union countries was made.
Keywords: кооперативні організації споживачів; товарні кооперативи споживачів; кредитні кооперативи; житлові кооперативи; страхові кооперативи; енергетичні кооперативи; медичні кооперативи; інформаційно-технологічні кооперативи; кооперативний сектор економіки; кооперація; cooperative organizations of consumers; commodity consumer cooperatives; credit cooperatives; residential cooperatives; insurance cooperatives; energetic cooperatives; medical cooperatives; IT cooperatives; Cooperative sector of economics; cooperation